Preparation of MnOx Supported LiOH Activated Soybean Oil Sludge Catalyst and Its Analysis in Denitration Mechanism of Selective Catalytic Oxidation (SCO) - Zhang Lei (Nature Portfolio, 2019)
Abstract Treatment with selective catalytic oxidation (SCO) is an effective technology applied recently for conversion of nitrogen oxides pollution control. In order to solve the problems of high cost and difficulties in practical application of SCO catalyst, it was put forward using the solid waste sludge from soybean oil plant as catalyst carrier to prepare denitration catalyst. The sludge was treated by alkaline activation and then MnOx-based sludge was prepared by impregnation. Finally, MnOx-based sludge was calcined in the muffle furnace. The effects of activation and calcination conditions on catalyst activity were investigated. Fourier transform infrared (FTIR), X-ray photoelectron spectroscopy (XPS), X-ray diffraction (XRD) and scanning electron microscopy (SEM) were used to characterize the activity of the sludge based denitration catalyst, and the structure and activity of the sludge based denitration catalyst were furtherly confirmed. According to the achieved results, (1) after activated by LiOH with a mass concentration of 15% for 4 hours, the surface of the sludge catalyst has more alkali functional groups, making the denitration of sludge catalyst the best; (2) the MnOx-based catalyst calcined in the muffle furnace with calcination temperature of 450 °C for 4 hours has obvious denitration efficiency.